Pressures on public sector pay - Jonathan Cribb; Magdalena Domínguez; Andrew McKendrick (Institute for Fiscal Studies (IFS), 2024)
Over a fifth of government spending goes on pay. We examine recruitment and retention challenges which mean that pressures could mount going forward.
Keywords: 330; Education and skills; Government finances and spending; Health and social care; Education; Living standards; NHS; Pay; Public finance; Public sector